A Study of Recruitment Methods in Canada’s Largest Industrial Concerns - Alpander, Guvenc (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author studies the recruiting methods practiced nowadays in the larger firms of Canada. He makes recommendations eliminating situations which could minimize or even impeach the due process of these methods.